PELAKSANAAN KEBIJAKAN KEMENTERIAN HUKUM DAN HAM TENTANG PEMBINAAN DAN PENDAYAGUNAAN PEJABAT FUNGSIONAL PERANCANG PERATURAN PERUNDANG-UNDANGAN PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM PROVINSI BALI - hutapea, bungasan (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2019)
This writing aims to examine the extent of fostering the Functional Position of Legislative Regulations in the region, whether the Policy of the Ministry of Law and Human Rights concerning the Development and Utilization of Designer Functional Officials can be carried out in the regions as mandated by PP RI No. 59/2015 article 5 paragraph (2) concerning the participation of designers in the formation of legislation. Phenomenon in the field shows that the designer in charge of the Regional Office of Law and Human Rights has not been optimally involved in the formation of regional regulations. Other factors identified were, where the lack of socialization about the urgency of involving designers in the making of Regional Regulations so that there was no synergy between the offices of the Legal and Human Rights Areas and the Regional Government. This paper is carried out by using a descriptive method that illustrates how the implementation of policies for the development and utilization of legislative functional officials at the regional level. Recommending the Directorate General of PP Coordinate with the Head of the Legal and Human Rights Development Agency so that the designer's functional training focuses more on the subject matter of the Regional Regulation Preparation Process to the designer in charge of the Regional Office of Law and Human Rights